Examining the factors of bank performances interact with the causes of 2007- 2008 financial crisis under the ‘black swan’ theory: empirical evidence from UK banks. - SU, YATING (2017)
The objective of the paper is to test the determinants which are significant related to the bank performance under the theoretical concept of the “Black swan” events. First of all, we discussed the concepts of the “Black swan” events which showed that the global financial crisis is one of the phenomenon to reflect the consequences of the event. Then we discussed the global financial crisis and the UK banking system. Secondly, the internal (bank-specific) and external (industry-specify and macroeconomic environment) factors on the bank performance in the financial crisis period (from 2008 to 2011). After combing the results for the models, liquidity risk and credit risk have negative and significant impact on the bank performance. These two variables are the most important factors for the bank performance during the financial crisis period.